Gender, race, and credit rationing of small businesses: empirical evidence from the 2003 Survey of Small Business Finances - Mijid, Naranchimeg, author; Bernasek, Alexandra, advisor (Colorado State University. Libraries, 2009)
Rapid rates of growth of small business ownership among women and minorities have motivated research on issues related to small business performance. The importance of access to credit for the success of small businesses, as well as evidence that women and minorities have less access to credit than male and white business owners has led researchers to explore the reason for this. The purpose of this study is to determine whether credit rationing in the small business credit market is different based on gender and/or race of the business owner. This study examines two types of credit rationing and uses a comprehensive measure that includes discouraged borrowers. In addition, we examine how loan amounts are determined. We utilize three different types of methodologies to analyze data from the 2003 Survey of Small Business Finances. Our results are consistent with previous studies that have found higher loan denial rates and lower loan application rates among women and minority business owners. Testing the robustness of the results, we find an asymmetry in the response of women business owners compared with minorities. The results suggest that women tend to ration themselves in the credit market, whereas minorities are rationed by banks through what appear to be prejudicial lending practices. The results for discouraged borrowers that estimate joint decisions of lenders and borrowers suggest that among those who apply for a loan, minority-owners have a higher chance of approval. This indicates that only higher quality firms apply for a loan, confirming the discouraging effect of banks' probabilistic offers. We also find that women and minority owners are more likely to be given a smaller loan than they request (type 1 rationing) than men and white owners. In addition, women-owned firms receive significantly smaller loan amounts than men-owned firms. There is no difference, however, in the approved loan amount between minority and white-owned firms.
Keywords: credit rationing; entrepreneurial finance; entrepreneurship; gender; gender and race; race; small business finance; small businesses; survey of small business finances; finance; gender differences; polls and surveys; racial differences; studies; gender studies; minority set aside programs; minority and ethnic groups